PENGARUH PRIVAT LABEL TERHADAP KESADARAN MEREK DAN CITRA MEREK PADA KONSUMEN FOODMART (STUDI KASUS PADA FOODMART DI KOTA) - Sarifuddin Sarifuddin (Jurnal Cita Ekonomika, 2020)
Private label is a product with a brand that can only be found in retail outlets. Private labels compete fiercely with producer brand products. This research was conducted to determine customer perceptions of private label, brand awareness and brand image and to analyze the effect of private label on brand awareness and brand image. The hypothesis formulated in this study consists of (1) there is an effect of private label variables on brand awareness, (2) there is an effect of private label variables on brand image, (3) there is an effect of brand awareness on brand image. This type of research is descriptive and verification with descriptive and explanatory survey research methods. Data obtained through questionnaires, interviews and field observations. The results of data collection with primary data sources were obtained from a total sample of 115 respondents. The method used is Structural Equation Modeling (SEM). The results showed that the private label variable had a significant effect on the awareness of the peacock, and the private label variable had a significant effect on brand image, and the variable brand awareness had a significant effect on the brand image.